A water-ammonia heat transformer to upgrade low-temperature waste heat. (25th December 2017) - Garone, Silvia; Toppi, Tommaso; Guerra, Marco; Motta, Mario
Highlights: A prototype water-ammonia heat transformer was built. The machine operates stably and reacts well to step variation of inlet conditions. It allows recovering waste heat at around 60 °C up to 85 °C. Thermal COP ranges between 0.4 and 0.475. Performances are at least comparable with those of other prototypes. Abstract: A prototype water-ammonia absorption heat transformer has been built and thoroughly tested. Compared to water-salts mixtures, water-ammonia allows operating the machine in a lower temperature range, fostering recover of low-grade heat. Driving temperatures between 60 °C and 64 °C were tested, with condenser temperatures of 8–16 °C. The unit proved able to operate in a stable, reliable and repeatable way in this working range, achieving gross temperature lifts up to 25 °C and thermal COPs in the range 0.400–0.475. Useful effect up to 4.5 kW was achieved, with electric consumption always below 100 W.